An evaluation of the predictive validity and reliability of ventilatory threshold - Amann, M.; Subudhi, A. W.; Walker, J.; Eisenman, P.; Shultz, B.; Foster, C. (Medicine & Science in Sports & Exercise, 2004)
Purpose: To identify a valid and reliable method to determine 40-km time trial (40K) performance in a laboratory setting. Methods: Part 1: Ventilatory threshold (VT) and 40K performance were determined on two occasions (February/September) using two subsets of cyclists (N = 15 each; [latin capital V with dot above]O2max 67.6 +/- 4.2/71.5 +/- 3.0 mL[middle dot]kg-1[middle dot]min-1) to determine the predictive validity of VT assessments. Variables of interest were power output at VT, peak power output (MaxVTW), and average power output during 40K (40Kavgwatts). For VT determination we used: breakpoint of VE/[latin capital V with dot above]O2; breakpoint of VE/VCO2; V-slope; RER = 1; and RER = 0.95. In part 2, test-retest reliability of VT and MaxVTW were examined in 20 subjects ([latin capital V with dot above]O2max 64.8 +/- 8.0 mL[middle dot]kg-1[middle dot]min-1) on two occasions, separated by 48 h. Results: Regression analyses between power outputs at VTs and 40Kavgwatts showed significant predictive validity for (February/September): V-slope (r = 0.79/0.84; SEE 15.5/13.3W), VE/[latin capital V with dot above]O2 (r = 0.80/0.81; SEE 15.2/14.2W), RER0.95 (r = 0.73/0.58; SEE 17.4/21.2W), RER1 (r = 0.75/0.74; SEE 16.8/16.7W), and MaxVTW (r = 0.81/0.73; SEE 15.0/17.1W). Paired t-tests between power outputs at VTs and the 40Kavgwatts indicated that mean power outputs at VE/[latin capital V with dot above]O2 (261 +/- 29W; P = 0.33) and RER0.95 (274 +/- 55W; P = 0.93) in February and VE/[latin capital V with dot above]O2 (274 +/- 37W; P = 0.79) in September were not significantly different from the respective 40Kavgwatts (277 +/- 30W/281 +/- 30W). Test-retest reliability analysis yielded the following intraclass correlation and relative test-retest errors: V-slope: 0.98, 2.6%; VE/[latin capital V with dot above]O2: 0.95, 5.3%; RER0.95: 0.87, 9.8%; RER1: 0.94, 5.7%; VE/VCO2: 0.87, 12.1%; MaxVTW: 0.98, 2.6%. Conclusion: The high test-retest reliability and consistent ability to accurately predict athletes' 40Kavgwatts across a competitive season indicated that VE/[latin capital V with dot above]O2 was superior to the other evaluated methods.